ANALISIS KINERJA KEUANGAN PADA PERUM BULOG SUB DIVISI REGIONAL SAMARINDA (PERIODE 2016-2018) - Danna Solihin, Novel Ingan, LCA Robin Jonathan, (EKONOMIA, 2020)
The purpose of doing research is to analyze the Financial performance of the company's Growth on a Regional Sub-division Bulog Perum Samarinda 2016-2018 Period in terms of the ratio of the solvency ratio, liquidity ratio and the ratio of profitability, Activity .Data analysis technique used is a financial ratio analysis of liquidity (current ratio and quick ratio), solvency (total debt to asset ratio), profitability (net profit margin), and activities (asset turn over).Results of the study of the growth of the financial performance on a Regional Sub-division Bulog Perum Samarinda as measured by Current Ratio 2016-2017 and 2017-2018 period of decline. The growth of financial performance on a Regional Sub-division Bulog Perum Samarinda as measured with the Quick Ratio 2016-2017 and 2017-2018 period of decline. The growth of financial performance on a Regional Sub-division Bulog Perum Samarinda as measured by Total Debt to Total Asset Ratio 2016-2017 and 2017-2018 period of decline. The growth of financial performance on a Regional Sub-division Bulog Perum Samarinda as measured by Net Profit Margin period of 2016-2017 and 2017-2018 decline. The growth of financial performance on a Regional Sub-division Bulog Perum Samarinda as measured by Asset Turnover period of 2016-2017 and 2017-2018 has increased